Bactericidal activity of skin mucus and skin extracts of Catla catla and Channa striatus - Ranjini, Shanmugavel; Muniasamy, Samuthirapandi; Rameshkumar, Ganesan; Rajagopal, Thangavel; Sivakumar, Thangavel; Ponmanickam, Ponnirul (Acta Biologica Szegediensis, 2020)
Fishes counteract certain microbial attacks in water by producing antimicrobial proteins/peptides in their skin surface. The present study focused on screening the bactericidal activity of skin and skin mucus extracts of Catla catla and Channa striatus. The bactericidal activity was assessed against Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Proteus vulgaris, Aeromonas hydrophila, Staphylococcus aureus and Bacillus coagulans by disc diffusion method. The minimal inhibitory concentration was also determined. Protein profiles in skin and skin mucus extracts were analyzed by SDS-PAGE. Samples from both fishes showed antibacterial activity. Detailed analysis of individual protein and peptide would throw light on their medicinal importance to be used against pathogenic microbes.